Design and Biophysical Characterization of Poly (l-Lactic) Acid Microcarriers with and without Modification of Chitosan and Nanohydroxyapatite - Li, Liying (Polymers (Basel), 2018)
Nowadays, microcarriers are widely utilized in drug delivery, defect filling, and cell culture. Also, many researchers focus on the combination of synthetic and natural polymers and bioactive ceramics to prepare composite biomaterials for tissue engineering and regeneration. In this study, three kinds of microcarriers were prepared based on physical doping and surface modification, named Poly (l-lactic) acid (PLLA), PLLA/nanohydroxyapatite (PLLA/nHA), and PLLA/nHA/Chitosan (PLLA/nHA/Ch). The physicochemical properties of the microcarriers and their functional performances in MC3T3-E1 cell culture were compared. Statistical results showed that the average diameter of PLLA microcarriers was 291.9 ± 30.7 μm, and that of PLLA/nHA and PLLA/nHA/Ch microcarriers decreased to 275.7 ± 30.6 μm and 269.4 ± 26.3 μm, respectively. The surface roughness and protein adsorption of microcarriers were enhanced with the doping of nHA and coating of chitosan. The cell-carrier cultivation stated that the PLLA/nHA microcarriers had the greatest proliferation-promoting effect, while the PLLA/nHA/Ch microcarriers performed the strongest attachment with MC3T3-E1 cells. Besides, the cells on the PLLA/nHA/Ch microcarriers exhibited optimal osteogenic expression. Generally, chitosan was found to improve microcarriers with superior characteristics in cell adhesion and differentiation, and nanohydroxyapatite was beneficial for microcarriers regarding sphericity and cell proliferation. Overall, the modified microcarriers may be considered as a promising tool for bone tissue engineering.